(untitled) (Archives of Criminology, 1974)
Three follow-up studies were published, dealing with juvenile delinquents and young adult offenders, based on a random sample and material on: ‒ 100 boys charged with larcency, who during the period of the investigation in 1966 were barely 10-11 years old. This research concentrated in turn on all the 10-11 year-old boys charged with larcency and brought before a Juvenile Court in Warsaw; the follow-up period embraced 5 years; ‒ 358 former juveniles (10-16 years old) charged with theft in three districts of Warsaw and brought before a Juvenile Court in 1961-1962, whose further fate was investigated during the period when they were 17-20 years old and from among the same 243 former juveniles 13-16 years old, who in 1972 were already 24-27 years old; ‒ 17-20 year-old young adults released from 40 prisons throughout the country, after having served their sentences for various offences and whose subsequent recidivism was established during the course of 10 years from their release from prison in 1961. Two works, discussing the further recidivism of the juvenile delinquents, convicted for larcency obviously differ markedly regarding the age and follow-up period. The first work deals with the investigated up to the age of 15-16 only, the second also embraces the time when the former juveniles are already approximately 26 years old. However, both works unanimously emphasize the fundamental significance of early initiation of social maladjustment and demoralization for the prognosing of the rapidity and extent of recidivism. They stress the necessity to make use in practice as the only criterion for recidivism of juveniles, each new charge brought before a court and the number of times theft has been committed, being the subject of a given trial. Simultaneously these works reveal unanimously, that the majority of the juvenile delinquents charged with larcency, are brought up in families, which are unable to guarantee them the proper conditions for normal development and that in these families also many brothers of the juvenile delinquents charged with larcency revealed symptoms of social maladjustment and committed offences. The results of the studies under discussion also are unanimous as to the fact that with the majority of the juveniles could be found personality disorders. The material under discussion deserves special attention as regards the juvenile delinquents of the younger age groups. It is of great significance that many of the investigated 10‒11-year-olds charged with larcency committed theft already before. Long years of research, conducted by the Department of Criminology, Institute of Legal Sciences, Polish Academy of Sciences, testify to the fact that the majority of the juvenile delinquents charged with larcency and brought before Juvenile Courts are boys who already previously committed larcency more than once. Disturbance of the socialization process with these juveniles, usually reaches back to their early childhood, requires early discovery and interference at the earliest possible time in the form of surrounding the parents, brothers and sisters of the juvenile delinquent with care and also of controlling them. The results yielded by follow-up studies of the recidivism during a period of 10 years of the 17-20 year-old young adult offenders, released from prison in 1961, concentrate on young people whose recidivism is undoubtedly connected with serious social maladjustment already during their juvenility. Obviously one cannot identify these young adults released from prison with all the 17‒20-year-old young adults convicted by courts who received various sentences. The results of the follow-up studies of the young adult prisoners should contribute to the initiation of systematic, individual research regarding young adults convicted and receiving various prison terms and to the change of certain guiding lines of the penal and penitentiary policy in regard to young adult offenders.